2020
DOI: 10.1111/ced.14404
|View full text |Cite
|
Sign up to set email alerts
|

Reactive infectious mucocutaneous eruption: Mycoplasma pneumoniae ‐induced rash and mucositis and other parainfectious eruptions

Abstract: Summary Mycoplasma pneumoniae‐induced rash and mucositis is the most accurate diagnosis for patients with blistering mucocutaneous disease provoked by an infection. Recent literature suggests expansion of the name is required, as other infections have caused a clinically similar presentation. This review provides a concise update on current understanding of M. pneumoniae‐induced rash and mucositis and other reactive infectious mucocutaneous eruptions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
49
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(59 citation statements)
references
References 71 publications
0
49
0
3
Order By: Relevance
“…RIME requires identification and treatment of the underlying infection, supportive care, and potential antimicrobial and immunosuppressive therapies. In fact, the use of antibiotics to treat community acquired pneumonia in patients with RIME has been emphasized [ 69 , 70 ]. One study examined the role of etanercept treatment in RIME and showed that this therapy led to improvement in physical findings within 2 days of drug administration [ 71 ].…”
Section: Clinical Updatesmentioning
confidence: 99%
“…RIME requires identification and treatment of the underlying infection, supportive care, and potential antimicrobial and immunosuppressive therapies. In fact, the use of antibiotics to treat community acquired pneumonia in patients with RIME has been emphasized [ 69 , 70 ]. One study examined the role of etanercept treatment in RIME and showed that this therapy led to improvement in physical findings within 2 days of drug administration [ 71 ].…”
Section: Clinical Updatesmentioning
confidence: 99%
“…Typical target lesions which are raised are only found in patients with EM ( 34 ). Additionally, MP-induced rash and mucositis (MIRM) emerged as an entity in 2015, which mostly affects mucous membranes and has minimal or even absent cutaneous involvement ( 35 , 36 ). MIRM has a milder disease course than EMM and SJS/TEN ( 8 ).…”
Section: Discussionmentioning
confidence: 99%
“…At present, immunological pathology has garnered much attention ( 18 ). There are common antigenic components in cell membranes of the body and the cell membrane glycolipid antigen of MP ( 19 ). After MP infection, the inflammatory response produced by macrophages, neutrophils and lymphocytes infiltrating around the alveolar and bronchial vessels is the pathological feature of MPP autoimmunity ( 20 ).…”
Section: Introductionmentioning
confidence: 99%